Conservative treatment for amelogenesis imperfecta: A case report - Campos, Roberto Elias; Valdivia, Andrea Dolores Correia Miranda; De Freitas Santos-Filho, Paulo Cesar; De Souza Menezes, Murilo; De Oliveira, Osmir Batista [UNESP]; Soares, Carlos Jose (My University, 2014)
Amelogenesis imperfecta is a hereditary condition that can alter the thickness, color, and shape of tooth enamel. Recent adhesive materials and techniques have provided less invasive treatment options. This case report presents the treatment of a patient whose anterior teeth had color alterations, white spots, pits, and shape defects. Using a more conservative technique, the mandibular and maxillary anterior teeth were restored using veneer direct composite restorations. After 6 years, the restorations demonstrated no deterioration, and no pathology was seen in association with the rehabilitation.